Integrative taxonomy of the red-finned barb, Enteromius apleurogramma (Cyprininae: Smiliogastrini) from Kenya, supports recognition of E. amboseli as a valid species - Schmidt, Ray C.; Bart, Henry L. Jr.; Nyingi, Wanja Dorothy (Zootaxa, 2018)
Research on freshwater ecosystems in East Africa is providing a better understanding of the biodiversity in the region. Recent studies of the Kenyan barbs (Cyprininae: Smiliogastrini) revealed diversity within several nominal species from the region. In this study, we examine the molecular and morphological variation in the red-finned barb (Enteromius apleurogramma). The results of this study support the recognition of E. amboseli as a valid species that is endemic to the middle Athi River drainage in southern Kenya. Enteromius amboseli is geographically isolated and distinguished from E. apleurogramma in having longer posterior barbels, a shorter dorsal fin, and generally fewer scales in the longitudinal series. Genetic divergence between E. apleurogramma populations in Lake Victoria and Lake Kanyaboli, provide novel estimates for rates of molecular evolution in the group. Additionally, the biogeography of these barbs and the conservation status of E. amboseli are discussed.